Clinical Usefulness of Somatosensory Evoked Potentials for Detection of Peripheral Nerve and Brachial Plexus Injury Secondary to Malpositioning in Microvascular Decompression. Issue 6 (December 2015) - Ying, Tingting; Wang, Xuhui; Sun, Hui; Tang, Yinda; Yuan, Yan; Li, Shiting
Abstract : Purpose: Neurologic injury secondary to positioning is a significant perioperative problem and a common cause of patient injury in the practice of surgery. Somatosensory evoked potentials' (SSEPs) monitoring has also been noted useful in evaluating upper extremity conduction changes related to positioning. The purpose of this article was to evaluate the effectiveness of intermittent monitoring of SSEPs, which detects peripheral nerve and brachial plexus injury caused by malpositioning during microvascular decompression (MVD). This article will also discuss the etiology and pathogenesis of nerve injury after MVD and the means to prevent them. Methods: Intraoperative SSEP monitorings for 485 patients who underwent MVD surgery were reviewed. A greater than or equal to 50% decrease in SSEPs amplitude and/or a greater than or equal to 10% increase in latency are considered significant change to produce potential postoperative neurological deficit. Risk factors were reviewed and a Student t -test was performed for significant differences. Results: The overall incidence of position-related upper extremity SSEP changes was 2.89%. No patient with a reversible SSEP change developed a new postoperative deficit in the affected extremity. Patients with low body mass index, diabetes mellitus had a higher rate of brachial plexus injury during MVD. Gender, age, and operation duration did not increase the risk of brachial plexus injury. Of the 14 patients who had a significant change of SSEP, there were 6 ulnar nerve on the contralateral side and 8 median nerve on the ipsilateral side. All the changes occurred within 10 minutes after the patients were positioned. Conclusions: When positioning the patient for MVD with lateral position, careful attention should be paid to both the dependent (lower) arm extremities and the upper shoulders to prevent peripheral nerve injury. Additional precautions should be taken if the patient has a low body mass index or diabetes. Continuous intraoperative SSEP monitoring of ulnar/median nerve function is a valid and useful technique to minimize intraoperative neurologic injuries during surgery.